2012
DOI: 10.1177/1065912911431245
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Political Institutions and Congressional Responsiveness to Minority Interests

Abstract: Despite claims that diversity benefits the democratic process, critics question whether increased diversity significantly improves government responsiveness and accountability beyond electoral competition and constituency influence. The authors advance a diversity infrastructure theory to explain why and how minority legislators have kept minority interests on the congressional agenda. Using data on congressional hearings held on civil rights and social welfare from 1951 to 2004, the authors find that despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 36 publications
(32 reference statements)
2
30
0
Order By: Relevance
“…Are legislators who support restrictive voter identification laws more likely to exhibit bias in responsiveness against Latino constituents? Theories of inequality and minority political representation have focused on the policy representation that minority and identity groups achieve in legislatures (e.g., Casellas ; Grofman, Handley, and Niemi ; Mansbridge ; Minta and Sinclair‐Chapman ; O'Brien ; O'Brien and Rickne ; Rouse ; Williams ), but they have concentrated much less frequently on nonpolicy responsiveness by legislators to constituents. Some argue that constituency groups who do not receive policy representation from legislators may still receive some level of representation via actions taken by legislators outside of the policy realm (e.g., Cain, Ferejohn, and Fiorina ; Canon , Grose ).…”
mentioning
confidence: 99%
“…Are legislators who support restrictive voter identification laws more likely to exhibit bias in responsiveness against Latino constituents? Theories of inequality and minority political representation have focused on the policy representation that minority and identity groups achieve in legislatures (e.g., Casellas ; Grofman, Handley, and Niemi ; Mansbridge ; Minta and Sinclair‐Chapman ; O'Brien ; O'Brien and Rickne ; Rouse ; Williams ), but they have concentrated much less frequently on nonpolicy responsiveness by legislators to constituents. Some argue that constituency groups who do not receive policy representation from legislators may still receive some level of representation via actions taken by legislators outside of the policy realm (e.g., Cain, Ferejohn, and Fiorina ; Canon , Grose ).…”
mentioning
confidence: 99%
“…Gender and racial caucuses are a key source of diversity capacity in institutions. For instance, research on the impact of diversity in Congress identifi es racial and ethnic caucuses (the Congressional Black, Hispanic, and Asian Pacifi c American caucuses) and the newer Tri-Caucus comprised of members of the CBC, CHC, and CAPAC as agents of change that encourage information and resource sharing, enhanced communication, and collective action on behalf of racial and ethnic minorities (Minta and Sinclair-Chapman 2013 ). Through a diversity infrastructure that includes caucuses, task forces, and organized voting blocs, minority legislators have kept low-salience civil rights issues on the congressional agenda despite waning public interest.…”
Section: Building a Diversity Infrastructurementioning
confidence: 99%
“…Cameron, Epstein, and O'Halloran (1996) considered the impact of racial composition on the substantive representation of minority interests in Congress. These authors found that drawing districts to maximize the number of minorities elected diminishes substantive representation of minority interests, largely as a result of reducing electoral support for White Democrats (see also Epstein & O'Halloran, 1999;Grose, 2011;Swain, 1993; but see Minta & Sinclair-Chapman, 2013). Lublin (1997Lublin ( , 1999 has documented the interaction of African American and Latino voters in majorityminority districts, regional differences in racial representation effects, and indirect effects of Republican candidate emergence in districts surrounding majority-minority districts.…”
Section: Redistricting Guidelines Of the Vramentioning
confidence: 99%